Characterization of phosphorus sorption and microbial community in lake sediments during overwinter and recruitment periods of cyanobacteria. (November 2022) - Tu, Chengqi; Jin, Zhenghai; Che, Feifei; Cao, Xin; Song, Xinshan; Lu, Changyu; Huang, Wei
Abstract: The release of endogenous phosphorus from lacustrine sediment is a key element of freshwater eutrophication. The microbes in sediments may affect phosphorus migration and transformation during the growth of cyanobacteria, which may lead to the release of phosphorus from sediments and contribute to water eutrophication. To study phosphorus sorption and the microbial community structure in the overlying water and the vertical depth of sediments, samples in Meiliang Bay were collected during the dormancy and resuscitation phases of cyanobacteria. The results showed that there were high total phosphorus (TP) concentrations in the overlying water and sediment, with maximum values reached 0.24 mg L −1 and 1059 mg kg −1, respectively. Fitting by modified Langmuir model indicated that the partitioning coefficients (KP ) was, from greatest to least: bottom sediment (maximum of 0.923 L g −1 ) > middle sediment (0.571 L g −1 ) > surface sediment (0.262 L g −1 ). During the cyanobacteria resuscitation stage, the relative abundance of Proteobacteria (18.37%–33.56%), Chloroflexi (9.57%–17.76%), Cyanobacteria (0.38%–2.62%), and the Nitrospirota phylum Thermodesulfovibrionia (4.61%–10.14%) were higher than the dormant period of cyanobacteria, and bacteria with phosphorus-solubilizing (27.27%–52.01%) accounted for the majority. The redundancy analysis (RDA) found that the structure of the microbial communities in sediments was significant correlation with organic phosphorus (OP) (P = 0.002) during recruitment period of cyanobacteria, which would accelerate the conversion of OP into soluble inorganic phosphorus and then gets released from sediment to water. The most predominant phylum among phosphorus-solubilizing bacteria (PSB) is Proteobacteria, followed by Actinobacteriota, which were positively correlated with equilibrium phosphorus concentration (EPC0 ) (P < 0.05) during the cyanobacterial resuscitation phase. The sediments from the cyanobacteria resuscitation phase had phosphorus release risk and highlighted the significant role of the bacterial community. Graphical abstract: Image 1 Highlights: IP concentration mainly consisted of NaOH–P was highest. The modified Langmuir parameters were significantly correlated with some PSB. Risk of phosphorus release during the cyanobacteria resuscitation stage.